Pelatihan Bisol bagi Penyandang Tunarungu dan Tunawicara di SLB PSM Takeran sebagai Bekal Berwirausaha - Swasti Maharani; Yuni Nurhayati; Tri Anisya Putri; Verry Larofa Husada; Astri Damayanti; Nur Fajri Irfan (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2018)
Impairment is something that most people do not want. There is impairment due to congenital from birth and there is also impairment caused by accidents. For example is deaf and mute. People with hearing impairment have limited hearing, whereas mute sufferers have limitations in terms of oral /voice and many also experience less hearing. Deaf people and mute need skills to maintain their survival, in SLB PSM Takeran there are lessons that teach about skills, but the skills of students in SLB PSM Takeran not well distributed, the creative craft made by SLB students are still stored neatly in school. Therefore, need to given the training bisol (Bisnis Online) for the deaf and mute in SLB PSM Takeran. The training was followed by 12 deaf and mute students at SLB Takeran. The training was held for two days with demo material on how to create social media account starting from e-mail creation, facebook, twitter, instagram, bukalapak, blibli.com and so on, then how to upload photos of products to be marketed, how to send goods Through shipping services. The results of the training were analyzed by qualitative approach. The results of the qualitative analysis (based on observation and interview) show that all participants feel the new knowledge and skills, namely the skills of doing business online. In addition, it can provide entrepreneurial supplies for people with deaf and mute. The future plan after this training will be the establishment of a disability community in Kecamatan Takeran, where the community will develop their skills and be able to create jobs for people with disabilities. So as to create financial independence for persons with disabilities.